IMPLEMENTASI PENDIDIKAN PEREMPUAN DI PESANTREN SIROJUL FALAH MULYOREJO KABUPATEN JEMBER - Dian, Muhammad Solihin (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
Women have the same rights and obligations in obtaining a proper education, so that women can develop their potential. Women's education is also carried out in Islamic boarding schools, because Islamic boarding schools strive to be a learning vehicle for women so that they can develop their abilities well. From this background, the aim of this research is to describe women's education at the Sirojul Falah Mulyorejo Islamic Boarding School, Jember Regency. This research uses a qualitative approach. The results of the research show that women's education activities at the Sirojul Islamic Boarding School have been carried out well. In this Islamic boarding school, female students and Muslim mothers are required to understand nisa jurisprudence such as the laws of menstruation, postpartum and istihadloh, among other things. The reason for implementing women's education at the Sirojul Falah Islamic Boarding School is that many female students and Muslim mothers do not fully understand the nisa jurisprudence. This Islamic boarding school uses the Book of Women's Qodrat by Kyai Ahmad Kamaludin, the Head of the Mambaul Falah Islamic Boarding School. This activity is carried out every Friday, from one in the afternoon to three in the afternoon at the Sirojul Falah Mulyorejo Prayer Room. At the Sirojul Falah Islamic Boarding School, the implementation of women's education is carried out repeatedly, memorized and understood. They are very enthusiastic about studying this book, because they feel lucky if they understand the contents of the book.